Wound-healing activity of Algerian Lavandula stoechas and Mentha pulegium extracts: from traditional use to scientific validation. (4th March 2022) - Baali, Faiza; Boumerfeg, Sabah; Boudjelal, Amel; Denaro, Marcella; Ginestra, Giovanna; Baghiani, Abderrahmane; Righi, Nadjat; Deghima, Amirouche; Benbacha, Faycel; Smeriglio, Antonella; Trombetta, Domenico
Abstract: The aim of the present study has been to evaluate the antioxidant, antimicrobial and wound healing activity of Algerian Lavandula stoechas and Mentha pulegium methanol extracts (LE and ME, respectively) in order to scientifically validate their traditional use. After a preliminary phytochemical screening, a polyphenol profile characterization was carried out by RP-LC-DAD-ESI-MS/MS analysis. Antioxidant activity was evaluated by different in vitro assays such as DPPH, TEAC, FRAP and ORAC whereas antimicrobial activity was carried out against representative standard ATCC and clinical Gram-positive and Gram-negative strains as well as against Candida albicans . The wound healing activity of ointments containing 5% and 10% of LE and ME was investigated on Wistar albino rats. Different polyphenol classess (flavones, flavonols and phenolic acids) were identified with rosmarinic acid that was the most abundant compound in both extracts (5658.40 and 1201.35 mg/100 g of LE and ME, respectively). LE and ME have strong antioxidant activity, whereas they showed antimicrobial activity only against S. aureus . However, both 5% and 10% LE and ME ointments significantly accelerated the wound healing process in comparison with negative control, providing a scientific rationale for the traditional use of L. stoechas and M. pulegium aerial parts in the treatment of wounds.